Pengaruh Right Issue Terhadap Harga Saham Pada Perbankan Yang Terdaftar Di Bei Periode 2021-2023 - Hutabarat, S Febriana Theresia; Situmorang, Syafrizal Helmi; Muda, Iskandar (Politeknik Ganesha Medan, 2024)
A right issue is a business activity that has the potential to impact the quantity and value of shares available on the market and contains crucial information that shareholders may utilize to increase their earnings in the future. Since the market may respond to the rights issue announcement, the information contained in the announcement becomes significant. A right issue is a current share issuance in which the company grants its existing shareholders the right to purchase new shares. Each existing shareholder is given the option to purchase a number of new shares from the company at a predetermined price and time. The purpose of this research is to examining variations in the stock price before and after the right issue. This study was carried out on financial institutions that are listed on the Indonesia Stock Exchange between 2021-2023 period. Event research is often used to test the information content of an event, such as the notification of the rights problem. The sampling method using the purposive sampling method. 26 banking companiess were chosen as examples based on the predefined criteria. Secondary data from Yahoo Finance is the kind of data that was used. 2021-2023, daily stock price data from Indonesia Stock Exchange website . The Wilcoxon Signed Rank Test is used in the data analysis procedure by using the Eviews 12 program. The outcomes demonstrated that the outcomes yielded values of 0,0986; 0,4429; 0,1925; 0,0999. As a result, the analysis suggests that the price of the shares did not significantly change before or after the rights issuance.